Análise do cadastro de imóveis rurais nos municípios do Pantanal Mato-grossense - Batista, Cássio Nascimento (2014)
This study analyzes the National System of Cadastre of Rural Property (SNCR) as to its organization, results and as a tool for planning. Planning as a basic tool to achieve development is divided into three parts. The first is strategic planning that provides for the analysis of extensive range of data and use local advantages to achieve goals (second part). These are best established in a participatory way, bringing local actors to control, the third that connects the other two is the program of action. The proposed development is discussed from the ideas of equality and freedom of choice showing the population mobilization and participation as a decisive factor again. The territorial approach allows an analysis from the economics, politics and cultural view of the forces that will form the territory and processes of territorialization, deterritorialization and reterritorialization (T-D-R). Aspects and applications of Multipurpose Technical Cadastre tool are presented. The SNCR is detailed from legal establishment, data collecting, the required evidence until management responsibilities in your update. The federal cadastres were evaluated with emphasis on the Fiscal Cadastre of Rural Properties (CAFIR) of the Brazilian Internal Revenue Service(IRS) as its basic function, collect taxes. The results of SNCR linked to the development of the wetland are discussed, their failures and their successes are analyzed. The final conclusion is that the SNCR is trustworthy and updated and can be converted into a Multipurpose Technical Cadastre, which enriched by the territorial approach can extend the range of products offered to guide the restrictions on access and use of land along with technical - scientific research look for solutions to drive sustainable development to Pantanal.